The Effectiveness of the Padlet-Assisted RQA Model on Scientific Literacy in the Ecosystem Material Integrated With Islamic Values - Yasmin Husna Qurota Ainin; Sumiyati Sa’adah; Asrianty Mas’ud (FKIP - Universitas Riau, 2026)
Science literacy remains a challenge in science education in Indonesia, particularly regarding ecosystem topics, which tend to be presented theoretically and have not yet been integrated with Islamic values. This study aims to analyze the effect of the Reading, Questioning, and Answering (RQA) model, supported by Padlet, on students’ science literacy skills regarding ecosystem topics integrated with Islamic values. The study employed a quantitative approach using a quasi-experimental method and a non-equivalent control group design. The sample consisted of 50 seventh-grade students from MTs Darul Ihsan YUPPI in Bandung Regency, selected using purposive sampling. Data were collected through science literacy tests, skobservation sheets, and student reflection questionnaires. The results showed that the experimental class achieved an N-Gain score of 0.64 (moderate category), while the control class scored 0.27 (low category). The Mann–Whitney test revealed a significant effect on students’ science literacy skills (Sig. 0.036 < 0.05) with a moderate effect size of 0.30. The novelty of this study lies in the integration of Islamic values into ecosystem learning through the RQA stages, which support reflective, contextual, and collaborative learning. Thus, the Padlet-assisted RQA model is effective in improving students’ science literacy skills.